Author Correction: Temporal dynamic reorganization of 3D chromatin architecture in hormone-induced breast cancer and endocrine resistance - Yufan Zhou (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.